REKAYASA GAME EDUKASI ADAB DALAM BERSIKAP UNTUK ANAK KELAS 1-3 SEKOLAH DASAR BERBASIS ANDROID - Rohada Nurman; Ridwan A. Kambau (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2021)
Adab is a very important part of education that relates to attitudes and values, both individually and socially. This research is motivated by the phenomena that occur today as a reflection of the decline of adab. The attitude and morals of the nation are getting worse. Seeing the importance of the role of adab in human life, it should be more serious to think about the concept of introducing and inculcating adab in attitude. The purpose of this study is to design an application for learning etiquette in attitude with a media game approach to help children in the process of forming attitudes according to adab. In conducting this research, the type of research used is an experimental method with a qualitative approach. The data collection method used in this research is in the form of observation and literature study. The design method used is the waterfall method and the testing technique used is BlackBox. The result of this research are a form of android - based education game. An application that can be used as a media towards manners education Keywords: Adab, Attitude, Game